Impact of Hydrostatic Pressure Variations Caused by Height Differences in Supine and Prone Positions on Fractional Flow Reserve Values in the Coronary Circulation - Yoshitaka Kawaguchi; Kazuki Ito; Humihiko Kin; Yusuke Shirai; Ayako Okazaki; Keisuke Miyajima; Tomoyuki Watanabe; Mariko Tatsuguchi; Yasushi Wakabayashi; Yuichiro Maekawa (Journal of Interventional Cardiology)
Objectives. To examine the influence of hydrostatic pressure on fractional flow reserve (FFR) in vivo. Background. Systematic differences in FFR values have been observed previously in the left anterior descending artery (LAD), left circumflex artery (LCX), and right coronary artery (RCA). It has been suggested that as the hydrostatic pressure variations caused by the height differences between the catheter tip (mean aortic pressure (Pa)) and pressure-wire sensor (mean distal intracoronary pressure (Pd)) are small, intracoronary pressure need not be corrected. Methods. Resting Pd/Pa and FFR values in 23 patients (27 lesions) were measured and compared in supine and prone positions. These values were corrected by hydrostatic pressure influenced by height levels and compared. Height differences between Pa and Pd were calculated using coronary computed tomography angiographies. Results. In LAD, resting Pd/Pa and FFR values were significantly higher in the prone position than in the supine position (0.97 ± 0.05 vs 0.89 ± 0.04, P<0.001 (resting Pd/Pa); 0.81 ± 0.09 vs 0.72 ± 0.07, P<0.001 (FFR)). Conversely, in LCX and RCA, these values were significantly lower in the prone position (LCX: 0.93 ± 0.03 vs 0.98 ± 0.03, P<0.001 (resting Pd/Pa); 0.84 ± 0.05 vs 0.89 ± 0.04, P<0.001 (FFR); RCA: 0.91 ± 0.04 vs 0.98 ± 0.03, P=0.005 (resting Pd/Pa); 0.78 ± 0.07 vs 0.84 ± 0.07, P=0.019 (FFR)). FFR values corrected by hydrostatic pressure showed good correlations in the supine and prone positions (R2 = 0.948 in LAD; R2 = 0.942 in LCX; R2 = 0.928 in RCA). Conclusions. Hydrostatic pressure variations due to height levels influence intracoronary pressure measurements and largely affect resting Pd/Pa and FFR, which might have caused systematic differences in FFR values between the anterior and posterior coronary territories.